Fracture risk assessment in metastatic femurs: a patient-specific CT-based finite-element approach - Falcinelli, Cristina; Di Martino, Alberto; Gizzi, Alessio; Vairo, Giuseppe; Denaro, Vincenzo (Meccanica (Milan), 2020)
Present paper aims to contribute to the definition of an effective strategy for the quantification of fracture risk in metastatic femurs, by means of a finite-element (FE) computational approach based on a refined constitutive description of the bone tissue. Healthy bone and metastatic tissue are described by a linearly poroelastic approach, by accounting for the specific degradation of material properties in the metastatic regions as related to the computed tomography (CT) evidence. The bone-metastasis interaction is also modelled through a Gaussian-shaped graded transition of material properties for the bone around the metastasis. Fracture risk indications are furnished by defining a strain-based local index and by referring to local patterns of strain energy density. Proposed computational strategy is applied to a clinical case related to a patient with both femurs affected by multiple metastases. Subject-specific FE 3D models of right and left femurs are generated from CT images and their mechanical responses are simulated by addressing a functional compressive load. Comparisons with a standard linearly elastic formulation (EL), that simply models the metastases as a pseudo-healthy tissue with low levels of material density and stiffness, are performed. Proposed results highlight that the adopted refined constitutive description identifies higher fracture risk levels with respect to the EL formulation, resulting also in very different patterns of bone regions prone to failure. In the limit of a suitable calibration based on significant experimental evidence, the proposed strategy may improve the strength prediction in metastatic femurs, allowing for an effective assessment of fracture risk useful in clinical practice.